Characterisation of equine cytochrome P450s - Orr, Catherine (2016)
Cytochrome P450s (CYPs) are a superfamily of enzymes involved in the phase I metabolism of endogenous and exogenous substances. They are present in almost all forms of life and have been studied extensively, particularly in relation to human medicine, where knowledge of their activities is essential for predicting drug-drug interactions. In the horse, little is currently known about CYP-specific drug metabolism, which holds importance for animal welfare and for doping control within the horseracing industry where drug-specific metabolites are tested for on race days. Recently the first recombinant equine CYPs have been produced, allowing specific data on equine P450 activity to be gathered for the first time. During the current study,46 full-length P450 sequences were identified from the equine genome. RT-PCR analysis was then carried out on equine liver in order to detect hepatic expression of P450s across various families. After this, cold-induction (pCold) E. coli were used for production of recombinant P450 proteins for subsquent functional testing. Four recombinant equine P450s were successfully expressed (CYP1A1, CYP2A13, CYP2C92 and CYP2D50). Due to being the isoforms most likely to be involved in drug metabolism, rCYP2D50 and rCYP2C92 were selected to be screened against ten of the most commonly used horse drugs to identify potential substrates. rCYP2C92 appeared to metabolise all four NSAIDs tested (flunixin, ketoprofen, phenylbutazone and diclofenac), however presence of the known hydroxylated metabolites of diclofenac and phenylbutazone (4-hydroxydiclofenac and oxyphenbutazone, respectively) could not be confirmed despite being present within equine liver microsome and human recombinant CYP2C9 samples. In spite of the apparant acivity displayed by rCYP2C92 towards all four NSAIDs, no conclussions can be made about this enzyme’s role in NSAID metabolism due to a lack of known hydroxylated metabolite production.